The Internet of Things solutions in the process of eliminating waste according to Lean Management assumptions - Chomiak, Iwona; Żuraw, Szymon (Rozwiązania Internet of Things w procesie eliminacji marnotrawstwa według założeń Lean Management, 2019)
The Internet of Things solutions in addition to their most popular consumer use in the form of smartphones, smart watches and many smart home solutions have the potential to be used in a production environment for more effective work. Due to the number of processes taking place in such enterprises and the multitude of tools used, the possibilities of implementing such solutions are unlimited. Taking the example of the types of waste that occur in enterprises as detailed in the process of the development of the Lean Management concept, the authors of the article point to the possible use of the Internet of Things tools while eliminating waste, which reduces costs and creates a competitive advantage of the company. The considerations presented in the article were presented on the basis of conducted literature research and using such research methods as case analysis, direct participation of the authors in the selected cases and co-participating in observations
Informatyka Ekonomiczna = Business Informatics, 2019, Nr 2 (52), s. 29-40
Keywords: Internet of things; waste; lean management; marnotrawstwo